The great glorious goddamn of it all : a novel - Ritter, Josh (Hanover Square Press, 2021)
A sweeping novel about the last days of the lumberjacks is told by of one of the greatest lumberjacks of all who recounts tales rife with murder, mayhem, avalanches, and bootlegging in the tiny timber town of Cordelia, Idaho.